Effects of extracts from Corylopsis coreana Uyeki (Hamamelidaceae) flos on xanthine oxidase activity and hyperuricemia. (2nd October 2016) - Yoon, In‐Soo; Park, Dae‐Hun; Ki, Sung‐Hwan; Cho, Seung‐Sik
Abstract: Objectives: This study aims to investigate xanthine oxidase (XO) inhibitory activity and antihyperuricemic effects of Corylopsis coreana Uyeki flos extracts and the phytochemicals contained therein. Methods: Ethanolic extracts of the plant were prepared, and the extraction process was optimized with respect to flavonoid content and XO inhibitory activity. The optimized ethanolic extract was tested for its XO inhibitory activity and antihyperuricemic effects in potassium oxonate‐induced hyperuricemic mice. Key findings: The 80% ethanolic extract showed the highest total flavonoid content and in‐vitro XO inhibitory activity. In‐vivo studies demonstrated that the optimized 80% ethanolic extract could inhibit hepatic XO activity and significantly alleviate hyperuricemia at a relatively low oral dose (50 mg/kg) in mice. Additionally, an in‐vitro enzyme inhibition study showed that phytochemicals such as bergenin, isosalipurposide, quercetin and quercitrin may be the key constituents responsible for the observed antihyperuricemic effects of the extract. Conclusions: This study is the first report on the XO inhibitory and antihyperuricemic effects of C. coreana Uyeki flos extract, which can be therapeutically applied in treating hyperuricemia and gout.